Power system transient stability enhancement - Koh, Jun Wei (2019)
The high consumption and reliance on electricity has cemented the importance of transient stability. Transient stability studies define as the power system’s capability to remain in synchronism after large disturbances are applied to the system. Proportional Integral Derivative (PID) and Power System Stabilizer (PSS) controllers are researched upon to enhance the transient stability of the power system. A Single Machine Infinite Bus (SMIB) model is used to simplify the multiple order nonlinear system. The system performance will be evaluated by computer simulation using Simulink in MATLAB.